(untitled) (CAHIERS MAGELLANES-NS, 2024)
As a result of the emergence of the anthropocentric direction in world linguistics, serious attention was paid to the study of the problem of the human factor in language. Scientific-theoretical studies were created on the linguistic expression of a number of signs of a person and his perception of existence, knowledge of the material world, worldview, mentality, culture, social status, place in society. This ensured the development of such fields of linguistics as sociolinguistics, cognitive linguistics, psycholinguistics, pragmalinguistics, linguoculturology, and raised them to the qualitative level. In particular, one of the specific directions of the scientific paradigm of the new stage, in the field of pragmalinguistics, the context, the speech situation, the communication environment, the general knowledge of the speakers of the objective world and the language skills were studied on a large scale. Especially in modern linguistics, special attention is paid to the phenomenon of connotation, which creates the emotional-expressive function of the language, and the study of its linguistic features.